Tingkat Kecemasan lbu Hamil Primigravida Trimester Iii Dalam Menghadapi Persalinan Di Desa Mlirip Kecarnatan Jetis Kabupaten Mojokerto - Eka Praneswari, Veryudha; Anggraeni, Tina (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractMost women primigravid third trimester who come to the midwife for checkups often feel anxious, since the number of phenomena that occur in the community such as miscarruage, uterine infection, bleeding, large babies and scary stories about pregnancy and childbirth. This study was conducted to determine the level of anxiety primigravida third trimester in the face of labor. The method used in this study was a descriptive design. The population is all primigravida third trimester in the village district jetis districts mlirip mojokerto. Number or samples 25 people, total sampling technique. The variables anxiety primigravida third trimester in the face of labor. Data obtained by distributing questionnaires . After that is done editing, coding, scoring and tabulating. The results of research shows that the level of anxiety prirnigravida trimester 3 in the face of labor namely anxiety is a total pf respondents (40%). Prirnigravidas anxiety levels before delivery motivated by age, education, occupation, ever, or do not get information about labor. Hopefully this research will motivate health wokers lo provide counseling and information via prirnigravida lo be more active in gelling information about labor through various sources such as print media and electronic media. It is also hoped primigravida pregnant women actively attend classes in the local village which is very useful to discuss or seek knowledge and solutions of the anxiety she experienced which would be guided by a local midwife.Keywords: anxiety, prirnigravida, third trimester, labor